Peran Roh Kudus Dalam Memberikan Kemampuan Untuk Mengasihi Berdasarkan Roma 12:20 - Oktario Johan Pratama; Enggar Objantoro (Sekolah Tinggi Teologi Pontianak, 2024)
Love of the enemy is a central teaching in the Christian faith that challenges human faculties. This study explores how the Holy Spirit enables believers to love, even to those who have hurt or hurt them, according to the teachings of Romans 12:20. Using a qualitative literature study method through an analysis of academic and biblical literature, this study identifies three main roles of the Holy Spirit: providing inner strength beyond human capabilities, transforming a hardened heart into compassion, and enabling tangible action that brings peace. The research also uncovered three major challenges in ego love and self-esteem, the desire to expect return, and the difficulty of forgiving that can be overcome through the power of the Holy Spirit. The findings show that love for the enemy is not just a moral demand but a spiritual call that can be practically realized in the daily lives of believers. In conclusion, the Holy Spirit plays a crucial role in transforming the human heart so that it can present the love of Christ as a witness of life in a middle world full of conflict and continuity. Kasih kepada musuh merupakan ajaran sentral dalam iman Kristen yang menantang kemampuan manusia. Penelitian ini mengeksplorasi bagaimana Roh Kudus memampukan orang percaya untuk mencintai, bahkan kepada mereka yang telah menyakiti atau menyakiti mereka, sesuai dengan ajaran Roma 12:20. Dengan menggunakan metode studi kepustakaan kualitatif melalui analisis literatur akademik dan alkitabiah, penelitian ini mengidentifikasi tiga peran utama Roh Kudus: memberikan kekuatan batin yang melampaui kemampuan manusia, mengubah hati yang keras menjadi penuh belas kasih, dan memampukan tindakan nyata yang membawa damai. Penelitian juga mengungkap tiga tantangan utama dalam cinta ego dan harga diri, keinginan mengharapkan balasan, dan kesulitan mengampuni yang dapat diatasi melalui kekuatan Roh Kudus. Temuan menunjukkan bahwa kasih kepada musuh bukan sekadar tuntutan moral tetapi panggilan spiritual yang dapat diwujudkan secara praktis dalam kehidupan sehari-hari orang percaya. Kesimpulannya, Roh Kudus berperan krusial dalam mentransformasi hati manusia sehingga dapat menghadirkan kasih Kristus sebagai kesaksian hidup di dunia tengah yang penuh konflik dan kesinambungan.